Ecojustice Principles: Challenges for the Evangelical Perspective - Langmead, Ross (Journal for the study of religion, nature and culture, 1998)
It is clear to anyone who moves in Protestant evangelical circles that concern for the environment is infrequently expressed. I have never heard any sermons preached on the environment other than those I have preached myself. There is a flurry of books being written by evangelicals urging Christians to care for the environment, but with a couple of exceptions they are at the popular level and have a breath-less feel, as if they know they are late in jumping on the environmental bandwagon. There is an International Evangelical Environment Network, but its concerns are not widely discussed in the evangelical mainstream (see the websites at Evangelical Environment Network [UK] 1998; Evangelical Environment Network [USA] 1998). I know of no general evangelical text in missiology that mentions either the environment or ecojustices in its index.